Thiazolidinedione Use in Individuals With Type 2 Diabetes and Chronic Obstructive Pulmonary Disease - Yen, Fu-Shun; Wei, James Cheng-Chung; Yang, Yu-Cih; Hsu, Chih-Cheng; Hwu, Chii-Min (Frontiers in Medicine, 2021)
Few studies have investigated the effects of various antidiabetic agents on individuals with both type 2 diabetes mellitus (T2DM) and Chronic obstructive pulmonary disease (COPD). This study compared mortality, cardiovascular events and respiratory outcomes in individuals with both T2DM and COPD taking TZD versus those not taking TZD. From Taiwan’s National Health Insurance Research Database, 12 856 propensity-score-matched TZD users and nonusers were selected between January 1, 2000, and December 31, 2012. Cox proportional hazards models were used to calculate the risks of investigated outcomes. Compared with nonuse of TZD, the adjusted hazard ratios (95% CI) of TZD use were stroke 1.63 (1.21-2.18), coronary artery disease 1.55 (1.15-2.10), heart failure 1.61 (1.06-2.46), noninvasive positive pressure ventilation 1.82 (1.46-2.27), invasive mechanical ventilation 1.23 (1.09-1.37), bacterial pneumonia 1.55 (1.42-1.70), and lung cancer 1.71 (1.32-2.22), respectively. In patients with concomitant T2DM and COPD, TZD use was associated with higher risks of cardiovascular events, ventilation use, pneumonia, and lung cancer. Use of TZD in these patients should be supported by monitoring for cardiovascular and respiratory complications.